Strategi Personal Branding Make Up Artist (MUA) Peduli Lingkungan Melalui Media Sosial - Alessandra Maria Daniartha; Eka Nada Shofa Alkhajar (Universitas Sebelas Maret (UNS), 2024)
Personal brand is the perception of everything how others or oneself accept someone. One of the media that is currently widely used to sell personal brands is social media, and Indonesian people are known as active users of social media. Every makeup artist must have his own strategy to form an image that will become his trademark. Sarah Erial is one makeup artist who uses Instagram to form personal branding. The interesting thing about Sarah Erial is branding herself as a makeup artist who cares about the environment. This phenomenon is interesting because research on this topic is still rarely found